KERASIONALAN PENGGUNAAN OBAT BEBAS DAN OBAT BEBAS TERBATAS COMMON COLD DALAM UPAYA SWAMEDIKASI OLEH MASYARAKAT DI KECAMATAN GAJAHMUNGKUR KOTA SEMARANG - aqnes budiarti; dharmika wijaya sakti; tri murti andayani (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2007)
ABSTRACTThe research about rationality of using over the counter drugs common cold for self medication in district of Gajahmungkur Semarang has been carried out. Data gotten from the result of field survey which is using the questioners that has been filled by Gajahmungkur’s people. Data will be analyzed with non analytical descriptive method. Based on the survey result, knowing that people in Gajahmungkur’s district choosing OTC drugs especially analgetic, antihistamin and decongestan (66,4%). The evaluation of rationality of using drugs for common cold has result: 1) Drugs of choice for common cold is correct. 2) Correct patient are 92,1%. 3) Correct dosage form 96,0%. 4) The most adverse drugs happens is sleepy (53,4%). Key words: Drugs rationality, common cold, self medication, people in district of Gajahmungkur Semarang